FINANCIAL SYSTEM TAKING INTO ACCOUNT PRICING (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
Pricing-based financial systems are a key aspect of modern economies. Pricing plays an important role in financial systems because it determines the price of assets, goods and services, and influences the decisions of investors, consumers and producers. Analysis of pricing in financial systems allows us to understand how prices are formed in markets, what factors influence price changes, how they reflect supply and demand, and what mechanisms are used to regulate price processes.